Surface Properties of Al–Fe–Si Liquid Alloy Using Thermodynamic Database - Mehta, U.; Yadav, S. K.; Koirala, I.; Adhikari, D. (Journal of Nepal Physical Society, 2020)
Temperature-dependent interaction parameters for excess free energies of mixing of sub-binary systems of Al-Fe-Si ternary liquid alloys were optimised using the experiment data in the frame of Redlich-Kister (R-K) polynomials. These optimised parameters were then used to compute the partial excess free energy of sub-binary and ternary liquid alloys. The surface tension and surface concentration of sub-binary and the ternary liquid alloys were computed using Butler equation. The temperature dependent coefficients of R-K polynomials for excess surface tensions of the sub-binary systems were optimised which were then used to estimate the surface tension of ternary alloy using Chou, Kohler and Toop modelling equations at temperatures 1773, 1873, 1973 and 2073 K. The surface tension of the ternary alloy obtained using aforementioned models were found to be in good agreement from Fe and Al corners but some deviations were observed from Si corner.